2015
DOI: 10.2525/ecb.53.43
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Rattail Fescue Powder for Weed Management

Abstract: Controlling weeds through allelopathy is one strategy to reduce dependency on synthetic herbicides. We investigated possible allelopathic effects of rattail fescue (Vulpia myuros (L.) C.C. Gmel.). Water extract of rattail fescue inhibited root and shoot growth of cress (Lepidium sativum L.). Powder of rattail fescue also inhibited the root and shoot growth of cress in a concentration dependent manner. The effectiveness of the water extract and powder of rattail fescue on the cress root and shoot growth was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In glasshouse studies, residues of V. myuros significantly suppressed germination and seedling growth of other plant species, including both crop and weed species [40,41]. Yamamoto and Kato-Noguchi [41] found that water extract and powder of V. myuros were equally effective in suppressing the root and shoot growth of Lepidium sativum. Twenty-one phytotoxic compounds were identified from aqueous extract of V. myuros, accounting for 0.05% of the dry weight residue [42].…”
Section: Impact On Crop Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In glasshouse studies, residues of V. myuros significantly suppressed germination and seedling growth of other plant species, including both crop and weed species [40,41]. Yamamoto and Kato-Noguchi [41] found that water extract and powder of V. myuros were equally effective in suppressing the root and shoot growth of Lepidium sativum. Twenty-one phytotoxic compounds were identified from aqueous extract of V. myuros, accounting for 0.05% of the dry weight residue [42].…”
Section: Impact On Crop Yieldmentioning
confidence: 99%
“…V. myuros produces allelochemicals that suppress the growth of other plants. In glasshouse studies, residues of V. myuros significantly suppressed germination and seedling growth of other plant species, including both crop and weed species [ 40 , 41 ]. Yamamoto and Kato-Noguchi [ 41 ] found that water extract and powder of V. myuros were equally effective in suppressing the root and shoot growth of Lepidium sativum .…”
Section: Impact On Crop Yieldmentioning
confidence: 99%